PERBEDAAN KOMPOSISI MEDIA ADSORBEN KARBON AKTIF DAN ZEOLIT TERHADAP PENURUNAN FENOL LIMBAH CAIR DI PT. XYZ (Politeknik Kesehatan Kemenkes Bandung, 2021)
One of the food Industries which is has production waste with a value exceeding the threshold with a phenol content of 2.23 mg/l. the maximum phenol content in liquid waste According to minister of environment regulation no.5/2014 is 0.5 mg/ l., The purpose of this research was to determine the thickness variation of the activated carbon and zeolite adsorbent media in reducing phenol levels in wastewater. The research was experimental, research design: pre and post test without control using the thickness media 70 cm difference of activated coconut carbon and zeolite media, difference 1:1 (35cm & 35 cm) , difference 4:3 (40cm & 40cm) and difference 9:5 (45cm & 25cm), many repetitions 6 times. The population in this research were all production waste and the sample was part of the production waste which was taken to be treated with adsorbent media. The sampling technique was grab sampling, the sample size was 24 samples. The data collection technique is to check the phenol content, temperature and pH of the wastewater, and analyze the data using the One Way Anova test. The results of the difference ingredient 1:1, 4:3 and 9:5, the average reduction in phenol levels of waste was 1.44 mg/l, 1.09 mg/l and 0.72 mg/l, the percentage reduction was 60.65%, 70,22%, and 80.44%. There is a significant difference in the reduction in phenol levels in wastewater in this study. Suggestion: further research is needed on increasing the surface area of the filter media order to reduce levels below TLV.